2017
DOI: 10.1021/acs.inorgchem.6b03056
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-Mediated Synthesis of Bulky Lanthanide Porphyrin–Phthalocyanine Triple-Deckers: Electrochemical and Magnetic Properties

Abstract: Five heteroleptic lanthanide porphyrin-bis-phthalocyanine triple-decker complexes with bulky peripheral groups were prepared via microwave-assisted synthesis and characterized in terms of their spectroscopic, electrochemical, and magnetic properties. These compounds, which were easily obtained under our preparative conditions, would normally not be accessible in large quantities using conventional synthetic methods, as a result of the low yield resulting from steric congestion of bulky groups on the periphery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 61 publications
(45 reference statements)
0
18
0
1
Order By: Relevance
“…Heteroleptic lanthanide porphyrin (Por)-bisphthalocyanine (L 3 ) triple decker complexes (L 3 )Ln(L 3 )Ln(Por) (Ln = Tb(III) (3) and Dy(III) (4)) were synthesized via microwave-assisted preparation. 24 A complete electrochemical study showed that such complexes highlighted four one-electron oxidations and three one-electron reductions which are centred on the ligands. The oxidation and reduction potentials of the L 3 ligand were identified at 0.50 and −0.65/−1.10 V vs. Fc/Fc + , respectively.…”
Section: Phthalocyanine Based Single-molecule Magnetsmentioning
confidence: 99%
See 1 more Smart Citation
“…Heteroleptic lanthanide porphyrin (Por)-bisphthalocyanine (L 3 ) triple decker complexes (L 3 )Ln(L 3 )Ln(Por) (Ln = Tb(III) (3) and Dy(III) (4)) were synthesized via microwave-assisted preparation. 24 A complete electrochemical study showed that such complexes highlighted four one-electron oxidations and three one-electron reductions which are centred on the ligands. The oxidation and reduction potentials of the L 3 ligand were identified at 0.50 and −0.65/−1.10 V vs. Fc/Fc + , respectively.…”
Section: Phthalocyanine Based Single-molecule Magnetsmentioning
confidence: 99%
“…10). 73 Both coordinated and uncoordinated MeOH molecules can be removed by exposure to air in a single-crystal-to-single-crystal transformation giving the compound (24) (Fig. 10).…”
Section: Solvato Switching Of Singlemolecule Magnet Behaviourmentioning
confidence: 99%
“…[5b], Moreover, although the fabrication method of TbPc 2 reported by De Cian et al have been extensively used since 1985, the product yield (around 4 %) is relatively small , . In 2017, Jin and the co‐workers reported an unconventional microwave‐mediated synthesis of bulky Lanthanide porphyrin–Pc triple‐deckers, which can also be used to increase the yield of double‐decker complexes . The impressive study indicates that the search of new synthetic method for SMMs is very valuable.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, variously substituted 5,10,15,20tetraarylporphyrins were shown to be readily accessible in yields up to 43% via microwaveassisted cyclocondensation of different aryl aldehydes with pyrrole, using a minimum amount of propionic acid [18]. Thus, microwave irradiation, also useful in metalloporphyrin synthesis [17,19], appears as a straightforward one-pot practical methodology minimizing reaction time, amount of solvent, and work-up problems.…”
Section: Introductionmentioning
confidence: 99%